Collision and information error of topologies in clustering protocol - HAN Jiang-hong1; WEI Zhen1; CAI Zhi-wen1; HAN Dong3; WEI Zhen-chun1 (Tongxin xuebao)
After the analysis of the collision in the CSMA and TDMA multiple access methods,and information error of topologies information in clustering protocol,a measurement index is introduced for the information error,and several methods are given in order to improve the index.The algorithm is combined with IEEE 802.15.4 protocol,and remarkable simulation conclusions are drawn from NS2 with the analysis of the impact of communication distance and movement speed.